Selecting Communication Technologies for an Electrical Substation Based on the AHP - Azhar N.A.; Mohamed Radzi N.A.; Mustafa I.S.; Azmi K.H.M.; Samidi F.S.; Zulkifli I.T.; Abdullah F.; Jamaludin M.Z.; Ismail A.; Zainal A.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Traditional communication technologies for distribution substations will soon have difficulties meeting the needs of emerging applications. This is due to exponential population growth and future energy demands, necessitating a reliable and fast response from the grid. Moreover, to the best of our knowledge, academic work regarding selecting appropriate communication technologies within electrical distribution substations is scarce. Thus, this research aims to aid decision-makers in selecting the best communication technology for an electrical distribution substation. This study uses the Analytical Hierarchy Process (AHP) to shortlist, rank, and decide the most suitable communication technologies for an electrical substation based on its geographical location. Technical, economic, infrastructure, and service standards are the main criteria used for the selection. The weight obtained from the pairwise comparison for each criterion is based on the literature review and expert opinions. The results comprise rankings of communication technologies tailored to different demographic settings, including urban, suburban, and rural areas. These rankings are generated through a comprehensive pairwise comparison process, building upon the earlier comparative analysis. Additionally, a structured framework has been developed to select the most appropriate communication technology for electrical substations in urban, suburban, and rural areas. According to our study, fiber optics, Narrowband Power Line Communication (NBPLC), and Long Range (LoRa) technology are the most prominent communication solutions for urban and suburban regions. Meanwhile, satellite communication (SATCOM), NBPLC, and fiber optics are prominent in rural areas. 2023 The Authors.